PARENTAL PARENTING STYLES IN GUIDING 5-6 YEAR-OLD CHILDREN TO MEMORIZE SHORT SURAYS IN KARANG SEMBUNG HALL, MEREMBU VILLAGE, 2023/2024 - Eliza Ayunita (JOETAL: Journal of Education, Teaching and Learning, 2025)
This study aims to determine the parenting styles used by parents in guiding children to memorize short suras in Karang Sembung Hamlet and to identify the obstacles and solutions parents encounter in guiding children aged 5-6 years to memorize short suras in Karang Sembung Hamlet. This study employed a descriptive qualitative method. The data sources used were primary and secondary data. Data collection techniques included observation, interviews, and documentation. The primary data sources were obtained from field interviews with parents of children attending RA/TK (kindergarten). Secondary data sources were obtained from books, journals, theses, news, the internet, documents, and scientific literature related to the research topic. The study concluded that the parenting styles used to guide children to memorize short surahs in Karang Sembung Hamlet were authoritarian, implemented by two informants, permissive, and democratic. Inhibiting factors and solutions for parents in guiding children to memorize short surahs in Karang Sembung Hamlet included parental emotional stability, limited parental time, environmental factors, limited parental attention, and limited parental knowledge of the memorization process (murojaah). Meanwhile, the solutions implemented by parents include creating a conducive atmosphere, implementing a reward and punishment system, optimizing the roles of family members, providing motivation.